Zaria Forman: “I draw to portray the sublime beauty and vulnerability of polar ice” - United Nations Educational, Scientific; Cultural Organization; Anuliina Savolainen (The UNESCO Courier, 2025)
American artist Zaria Forman has accompanied NASA, the United States’ space agency, on missions documenting changes in Earth’s polar ice. Her large scale pastel drawings complement scientists’ observations by bringing to life the fragile beauty of icy landscapes.